2023
DOI: 10.1039/d3tb01203d
|View full text |Cite
|
Sign up to set email alerts
|

A robust yet simple method to generate fluorescent amyloid nanofibers

Abstract: Covalent tagging of fluorophores is central to the mechanistic understanding of important biological processes including protein-protein interaction and protein aggregation. Hence, studies on fluorophore-tagged peptides help in elucidating the molecular...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 41 publications
(63 reference statements)
1
6
0
Order By: Relevance
“…The red puncta shown in Figure c,d confirmed the internalized Trp fibrils, and such an interpretation is strongly supported by our control experiments in which we did not see any red puncta when only Rho-B was added to the cells (Figures a,b and S4). Our previous work has confirmed that the presence of Rho-B alone at the studied concentration does not show any cytotoxic effect . Efficient internalization of Trp fibrils into SH-SY5Y cells after their treatment seems to induce cellular damage as most of the cells were found to be deformed (Figures c and f,g).…”
Section: Resultssupporting
confidence: 68%
See 4 more Smart Citations
“…The red puncta shown in Figure c,d confirmed the internalized Trp fibrils, and such an interpretation is strongly supported by our control experiments in which we did not see any red puncta when only Rho-B was added to the cells (Figures a,b and S4). Our previous work has confirmed that the presence of Rho-B alone at the studied concentration does not show any cytotoxic effect . Efficient internalization of Trp fibrils into SH-SY5Y cells after their treatment seems to induce cellular damage as most of the cells were found to be deformed (Figures c and f,g).…”
Section: Resultssupporting
confidence: 68%
“…Our previous work has confirmed that the presence of Rho-B alone at the studied concentration does not show any cytotoxic effect. 20 Efficient internalization of Trp fibrils into SH-SY5Y cells after their treatment seems to induce cellular damage as most of the cells were found to be deformed (Figures 2c and 1f,g). To gain insights into the mechanism of Trp fibril induced cytotoxicity, we carried out acridine orange (AO) and propidium iodide (PI) double staining assays, and the results suggested apoptosis and necrosis mediated cell death (Figure 3a,b).…”
Section: ■ Results and Discussionmentioning
confidence: 96%
See 3 more Smart Citations